Clinical features of Hispanic thyroid cancer cases and the role of known genetic variants on disease risk. Issue 32 (August 2016) - Estrada-Florez, Ana P.; Bohórquez, Mabel E.; Sahasrabudhe, Ruta; Prieto, Rodrigo; Lott, Paul; Duque, Carlos S.; Donado, Jorge; Mateus, Gilbert; Bolaños, Fernando; Vélez, Alejandro; Echeverry, Magdalena; Carvajal-Carmona, Luis G.
Abstract : Abstract: Thyroid cancer (TC) is the second most common cancer among Hispanic women. Recent genome-wide association (GWA) and candidate studies identified 6 single nucleotide polymorphisms (SNPs; rs966423, rs2439302, rs965513, rs6983267, rs944289, and rs116909374), associated with increased TC risk in Europeans but their effects on disease risk have not been comprehensively tested in Hispanics. In this study, we aimed to describe the main clinicopathological manifestations and to evaluate the effects of known SNPs on TC risk and on clinicopathological manifestations in a Hispanic population. We analyzed 281 nonmedullary TC cases and 1146 cancer-free controls recruited in a multicenter population-based study in Colombia. SNPs were genotyped by Kompetitive allele specific polymerase chain reaction (KASP) technique. Association between genetic variants and TC risk was assessed by computing odds ratios (OR) and confidence intervals (CIs). Consistent with published data in U.S. Hispanics, our cases had a high prevalence of large tumors (>2 cm, 43%) and a high female/male ratio (5:1). We detected significant associations between TC risk and rs965513A (OR = 1.41), rs944289T (OR = 1.26), rs116909374A (OR = 1.96), rs2439302G (OR = 1.19), and rs6983267G (OR = 1.18). Cases carried more risk alleles than controls (5.16 vs. 4.78, P  = 4.8 × 10 −6 ). Individuals with ≥6 risk alleles had >6-fold increased TC risk (OR = 6.33, P  = 4.0 × 10 −6 ) compared to individuals with ⩽2 risk alleles. rs944289T and rs116909374A were strongly associated with follicular histology (ORs = 1.61 and 3.33, respectively); rs2439302G with large tumors (OR = 1.50); and rs965513A with regional disease (OR = 1.92). To our knowledge, this is the first study of known TC risk variants in South American Hispanics and suggests that they increase TC susceptibility in this population and can identify patients at higher risk of severe disease. Abstract : Supplemental Digital Content is available in the text